2020
DOI: 10.3892/etm.2020.9134
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance confocal microscopy characteristics of oral lichen planus: An analysis of 47 cases in a Chinese cohort

Abstract: Reflectance confocal microscopy (RCM) is a non-invasive tool that provides real-time microscopic images and relatively high-resolution tissue images. This technique provides a link between clinical examination and histopathology. RCM has been used to detect skin diseases and has also recently been applied to diseases of the oral mucosa. The present study aimed to explore the features of oral lichen planus (OLP) using RCM. A total of 47 patients with OLP exhibiting a reticular pattern, were included in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Seven studies in this review studied in vivo OPMD specimens with only one using a quantitative assessment method (Table 2). structures which corresponded to dilated vessels with inflammatory cell infiltration (Peng et al, 2020). The RCM features of OLP seen by these three studies were consistent with the ones reported in the review by Lucchese et al (2016) (Lucchese et al, 2016).…”
Section: In Vivo Opmdsupporting
confidence: 88%
See 2 more Smart Citations
“…Seven studies in this review studied in vivo OPMD specimens with only one using a quantitative assessment method (Table 2). structures which corresponded to dilated vessels with inflammatory cell infiltration (Peng et al, 2020). The RCM features of OLP seen by these three studies were consistent with the ones reported in the review by Lucchese et al (2016) (Lucchese et al, 2016).…”
Section: In Vivo Opmdsupporting
confidence: 88%
“…Inflammation and obscured connective tissue papillae were highlighted in the atrophic‐erosive lesions due to the lack of hyperkeratosis (Contaldo et al, 2019). Peng et al (2020) also noticed ring‐like bright structures at the epithelial‐connective tissue junction that were attributed to keratinocyte necrosis in their RCM OLP lesions. The authors noted dark lumen structures with bright round cells inside these structures which corresponded to dilated vessels with inflammatory cell infiltration (Peng et al, 2020).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Biopsy for histopathological confirmation of the diagnosis has been performed for any suspected malignancy as well as not conclusive confocal examination. The RCM evaluation was based on diagnostic criteria previously described in oral pathology or, when not available in literature, in the skin 3–23 . The features were evaluated for presence/absence (non‐parametric binary data) by three dermatologists (C.F., V.D.M.…”
Section: Methodsmentioning
confidence: 99%
“…After pilot studies to validate the method [93,106,107], research has focused on highlighting the peculiarities of various pathologies affecting the oral mucosa, such as oral lichen planus and other inflammatory oral diseases [108][109][110][111][112], pigmented lesions of the lips [113][114][115][116], and actinic cheilitis [117,118], as well as to define some "confocal features" peculiar of preneoplastic and neoplastic oral lesions [119][120][121]. The RCM indicators of OSCC overlap the conventional histologic criteria, except the classical OIN grading [122,123], which, being performed on transversal sections of the tissue, is not allowed by the horizontal virtual slicing obtained by in vivo RCM.…”
Section: In Vivo Confocal Microscopymentioning
confidence: 99%